Novel methods to induce complex coacervation using dual fluid nozzle and metal membranes: Part II – Use of metal membrane technology to induce complex coacervation - Ferreira, Sungil [UNESP]; Nicoletti, Vania Regina [UNESP]; Dragosavac, Marijana (Elsevier, 2023)
In this follow up study, which is the extension of our previous work on the use of metal membranes for production of ginger oil emulsions with engineered droplet size (part I), we continue the exploration of membrane technology for production of complex coacervates. In this paper (part II) we introduced a novel method to induce multi core complex coacervation using metal membrane technology - which has been most used for drop-by-drop emulsification. Gelatin (4% and 10% w/w) and ginger oil (gelatin to ginger oil ratio 1:1) emulsions were produced using the high shear homogenization followed by injection through the metal membranes to induce complex coacervation using gum Arabic at pH 3.5 using a dispersion cell. The capsules (coacervates) produced using metal membrane (with 24 µm pore diameter) had spherical shape with diameters between 53 and 72 µm. Encapsulation efficiency ranged between 61% and 93% while the encapsulation yield varied from 15% to 90%, being significantly higher for emulsions with 4% (w/w) of gelatin. Complex coacervation by metal membrane was compared with coacervation induced by atomization and batch stirring. The methods discussed in this study can be potentially used in encapsulation of both lipophilic and hydrophilic compounds. Finally considering encapsulation properties and the possibility of engineering the capsules size, the use of membrane technology is a promising new configuration to induce complex coacervation, with real possibilities to allow scale up of the process of complex coacervation.
Keywords: Atomization; Dispersion cell; Encapsulation; Gelatin; Ginger oil; Gum Arabic; Hydrocolloid matrix; Metal membranes